Men's age determines sexual and reproductive health services utilisation in Ekiti State, Nigeria - Oluwakemi Christie Ogidan; Adekemi Eunice Olowokere; Oladele Simeon Olatunya (Scientific African, 2024)
Objective: Sexual and reproductive health services are majorly patronised by women leaving -out the men, hence men's opinions are not usually known or reflected. Therefore, in this study, men's opinion on determinants of Sexual and Reproductive Health (SRH) service utilisation among men were established. This was done in a bit to plan specific and attractive sexual and reproductive health services for men Methods: A cross-sectional quantitative study was conducted among 339 men between the ages of 18 and 65 years. Study participants were selected at household level from twelve communities using multistage and systematic sampling. Data were collected with the aid of structured questionnaire. Data were analysed with SPSS IBM statistics version 26 and the statistical significance was set at p-value < 0.05. Results: Only 18 % had previously utilised SRH services. Age was the only predisposing characteristic found to be associated with SRH service utilisation (p = 0.02) while distance of hospitals to participants’ residence and distance of hospitals to participants’ office were enabling characteristics found to be significantly associated with SRH service Utilisation (p = 0.00 and p = 0.04), respectively. Prevention and treatment of HIV (p = 0.03) and prevention and treatment of male sexual dysfunction (p = 0.01) were the need-based characteristics associated with SRH service utilisation. Binary logistic regression analysis showed that only age (OR = 1.40, 95 % C. I=1.03–1.90, p = 0.03) was the significant determinant of SRH service Utilisation with middle-aged men utilising SRH services more than other age groups. Conclusion: The utilisation of SRH services by men in this study was poor and this was majorly due to barriers that were service provision related. The study established that age is a major determinant of SRH utilisation by men. Age is an important factor while establishing SRH services for men, hence the need to set up specific MSRH services that are age appropriate and appealing to men.